Proceso de atención de enfermería en adulto mayor de 71 años con gangrena de Fournier. - Veliz Pino, Lissette Roxana (2021)
Fournier's gangrene is a rare and life-threatening infectious disease characterized by necrotizing fasciitis of the perineum and abdominal wall in men, as well as the scrotum and penis. Skin loss can be very disabling and difficult to resolve. Fournier's gangrene is a progressive and fulminant infection, a true surgical emergency, through timely treatment, including early surgical intervention, treatment with broad-spectrum antibiotics. The purpose of this clinical case is to present the nursing care process of a 71-year-old patient from the Gustavo Domínguez Hospital, with a diagnosis of Fournier's gangrene at the scrotal level with a four-day course with a necrotic characteristic that produced pain and fever, the medical staff ordered complementary laboratory tests, due to the results obtained he was immediately transferred to the surgery area for subsequent transfer to the operating room. With Marjory Gordon's nursing assessment by functional patterns, the diagnosis was determined, the appropriate care of the nursing care process is provided, which is based on the theory of Virginia Henderson to address basic human needs and solve problems of pathology and continue to improve the patient's health.